Health Promotion in Public Places of Sakinah Supermarket Surabaya - Zulfia Husnia; Hario Megatsari (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2020)
Background: Humans daily activities are inseparable from public places. Public places are facilities used for communal public activities, such as buying and selling in supermarket. The management of supermarkets have to ensure clean, healthy, safe, and comfortable facilities which do not give disadvantages for health. In responding this issue, health promotion is required in public places to get rid of environmental pollution and disease transmission. Objective: This study described health promotion in public places as found in Sakinah Supermarket. Method: This study was descriptive research with a quantitative approach. Data were categorized into primary data through observation and in-depth interview, as well as secondary data through Sakinah Supermarket’s document. The analysis was explored by using Ottawa Charter's 5 means of action as basic health promotion tool. Results: Health promotion in Sakinah Supermarket was still lacking. Health promotion efforts that have been done well are the concept of a No-Smoking Area, where Sakinah Supermarket did not sell cigarettes and did not provide smoking area. Conclusion: Sakinah Supermarket has not supported healthy public places since it does not give adequate information to improve individual’s awareness of health.